1982
DOI: 10.1007/bf00432774
|View full text |Cite
|
Sign up to set email alerts
|

The presence of 7-hydroxychlorpromazine in CSF of chlorpromazine-treated patients

Abstract: 7-Hydroxychlorpromazine (7-OHCPZ) has been identified and quantified in CSF from chlorpromazine (CPZ)-treated schizophrenic patients. The level of the metabolite in CSF was similar to that of CPZ. In serum the amount of 7-OHCPZ was about 30% of CPZ. The concentration of 7-OHCPZ in csf was positively and significantly correlated to the serum level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Different antipsychotic drugs and drug metabolites may, however, have different 44 blood-brain distribution ratios because of differences in protein binding in both plasma and CSF (Alfredsson et al 1982(Alfredsson et al , 1984aNyberg et al 1981;Wode-Helgodt & Alfredsson 1981). The dopamine receptor-blocking activity in plasma of psychiatric patients may, therefore, not be directly correlated to neuroleptic-induced dopamine receptor-blocking activity in the brain.…”
Section: Influence Of Blood-brain Distribution On Results Using Radiomentioning
confidence: 91%
See 2 more Smart Citations
“…Different antipsychotic drugs and drug metabolites may, however, have different 44 blood-brain distribution ratios because of differences in protein binding in both plasma and CSF (Alfredsson et al 1982(Alfredsson et al , 1984aNyberg et al 1981;Wode-Helgodt & Alfredsson 1981). The dopamine receptor-blocking activity in plasma of psychiatric patients may, therefore, not be directly correlated to neuroleptic-induced dopamine receptor-blocking activity in the brain.…”
Section: Influence Of Blood-brain Distribution On Results Using Radiomentioning
confidence: 91%
“…7-Hydroxy chlorpromazine also has an antipsychotic effect when administered directly to patients (Kleinman et al 1980), and it reaches cerebrospinal fluid (CSF) concentrations in the same range as that of the parent drug, chlorpromazine, after oral administration (Alfredsson et al 1982). However, no significant contribution from 7-hydroxy chlorpromazine and N-monodesmethyl chlorpromazine to therapeutic response could be found in a study by Wode-Helgodt et al (1978).…”
Section: Thioridazine and Chlorpromazinementioning
confidence: 94%
See 1 more Smart Citation
“…In work conducted by other investigators 7-hydroxy-CI'Z was the most potent CPZ metabolite in its ability to increase plasma prolactin levels subsequent to injection in male rats (Meltzer et al 1977), to bind to alpha-1 adrenergic receptors (Hals et al 1986), to increase the levels of homovanillic acid in rat striatum (Krieglstein et al 1980), and to block amphetamine-induced stereotyped behaviour in rats (La1 and Sourkes 1972). Moreover, 7-hydroxy-CPZ attains concentrations in the cerebral spinal fluid of psychiatric patients that are equal to CPZ (Alfredssen et al 1982). It has been demonstrated that patients responding favorably to CPZ therapy have higher plasma levels of 7-hydroxy-CPZ (Salialis et al 1973, Mackay et al 1974.…”
Section: Discussionmentioning
confidence: 98%
“…Thus specified patients may not demonstrate therapeutic benefit with a particular class of phenothiazine because in addition to inter-individual variations they could be essentially 'metabolic nonresponders' (Sakalis et al 1973, Mackay et al 1974, Perel and Manian 1977, Alfredssen et al 1982.…”
Section: Introductionmentioning
confidence: 99%